A CONTENT ANALYSIS ON THE FEATURE OF VOCABULARY IN “GROW WITH ENGLISH HANDBOOK” - airin malau; ira sinaga; rinita simamora (ELT (English Language Teaching Prima Journal), 2025)
This investigation seeks to identify and scrutinize the typologies of vocabulary exercises incorporated within the "Grow with English" textbook designed for Grade 4 students. Vocabulary acquisition is fundamentally crucial to language learning, particularly at the elementary level where learners are establishing foundational linguistic competence. This textbook, extensively utilized in Indonesian primary education, is structured to support English acquisition through diverse and engaging pedagogical activities. Employing a content analysis methodology, this research systematically examines the vocabulary tasks presented in each unit of the Grade 4 textbook. The exercises were subsequently categorized according to established activity formats, such as picture-word matching, multiple-choice questions, cloze (fill-in-the-blank) tasks, crossword puzzles, and word searches. The findings reveal a predominance of matching and fill-in-the-blank activities, which are specifically aimed at developing both lexical recognition and contextual comprehension. While more interactive formats, including crossword puzzles and word searches, are also incorporated, their frequency of appearance is comparatively lower. The diversity of exercise types suggests the textbook endeavors to provide a balanced and stimulating approach to vocabulary development. This study is anticipated to contribute to the evaluation and refinement of English instructional materials, particularly concerning the selection of effective vocabulary pedagogy for primary learners. Furthermore, the results may serve as a valuable reference for educators in designing or supplementing classroom vocabulary interventions tailored to student requirements.